Aplikasi Enkripsi dan Dekripsi Teks Menggunakan Algoritma Merkle Hellman - Purba, Lamrianto; Ginting, Guidio Leonarde (MEANS (Media Informasi Analisa dan Sistem), 2019)
Cryptography is the science and art of keeping messages safe. In cryptography there are two main concepts, namely encryption and decryption. The encoding is first created using the clasic algorithm. this algorithm builds security on the confidentiality of the algorithm used. But this algorithm is not efficient when used to communicate with many people because the algorithm is still very simple and still very easy to solve, so that important information or data that can be easily kept secret can be recognized by other people or irresponsible people. Merkle Hellman algorithm is a cryptographic algorithm that generally encrypts twice or also called double, namely plainteks encrypted with cipher I, then the first encryption results are encrypted again with cipher II.